Deux joueurs mais un jeu - Alain Farah (Contextes)
Dedicated to the analysis of “Le roman mode d’emploi”, an interview between Olivier Cadiot, Jean Echenoz, and Minh Tran Huy published in 2007 in Le Magazine littéraire, this article attempts to observe the operational dimension of the border formerly drawn by Pierre Bourdieu between the spheres of large and small scale production, as well as the editorial and journalistic strategies that configure contemporary literary space. Its aim is thus to identify how the crossed style of the exchange appears at first glance conducive to a “reclassification” of Olivier Cadiot, a writer who has been previously deemed “difficult”, into an author now accessible to the general public. This exercise in literary sociology, which borrows concepts and tools from Bernard Lahire and Charlotte Nordmann, shows the ways in which Echenoz and Cadiot, two writers who are also “close friends”, get caught up in the game of the interview, to the point where the classifications associated to Bourdieu’s polarity are confounded and reconfigured.